2016
DOI: 10.1155/2016/8734309
|View full text |Cite
|
Sign up to set email alerts
|

Nonlethal Levels of Zeaxanthin Inhibit Cell Migration, Invasion, and Secretion of MMP-2 via NF-κB Pathway in Cultured Human Uveal Melanoma Cells

Abstract: Zeaxanthin at nonlethal dosages (3–10 μM) significantly inhibited the cell migration of cultured uveal melanoma cells (C918 cell line) as determined by wound healing assay and Boyden chamber assay. Matrigel invasion assay showed that cell invasion of uveal melanoma cells could be significantly inhibited by zeaxanthin. Secretion of MMP-2 by melanoma cells was significantly inhibited by zeaxanthin in a dose-dependent manner as measured by ELISA kit. Zeaxanthin also significantly inhibited the NF-κB levels in nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…The zeaxanthin-rich extracts from Goji Erma (1) and Biglifeberry (2) inhibited at some extent the fibroblast proliferation in vitro, these results being in accordance with previous studies [ 7 ]. Zeaxanthin effect was dissimilar to those of glycoconjugates from Goji, which promoted the survival of human fibroblasts [ 20 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The zeaxanthin-rich extracts from Goji Erma (1) and Biglifeberry (2) inhibited at some extent the fibroblast proliferation in vitro, these results being in accordance with previous studies [ 7 ]. Zeaxanthin effect was dissimilar to those of glycoconjugates from Goji, which promoted the survival of human fibroblasts [ 20 ].…”
Section: Discussionsupporting
confidence: 91%
“…The upregulation of the NF-kβ indicates cancer progression, and many natural products were identified as blockers of this signaling pathway [ 39 ]. In the case of L. barbarum extracts 1 and 2 , no inhibition of p65 intracytoplasmic translocation was observed in A375 cells ( Figure 5 ), while in uveal melanoma the inhibition of NF-kB pathway was reported [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 23 MMPs identified in humans [ 19 ], MMP-2 is widely expressed in tissues and cells [ 20 ]. Recently, the levels of MMP-2 secretion were directly used to evaluate the migration of various types of cells [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further experimental evidence indicated that MMPs mediate UM cell invasiveness in vitro [112] and in xenograft models. Indeed, inhibition of MMP2 expression and/or activity by epigallocatechin gallate [113] or zeaxanthin [114] inhibited UM cell invasiveness, supporting a potential role of MMP2 inhibitors in the prevention of UM metastases.…”
Section: Targeting Hyper-expressed Molecules Involved In Progressionmentioning
confidence: 99%